PERANAN DEPARTEMENT HUMAN RESOURCE DEVELOPMENT (HRD) DALAM UPAYA MENINGKATAN KOMPETENSI PEGAWAI DI SAAT PANDEMIC COVID-19 DAN ERA NEW NORMAL PADA ORGANISASI PERUSAHAAN - Yusriadi, Yusriadi (Eko dan Bisnis: Riau Economic and Business Review, 2021)
The impact of the Covid-19 pandemic has affected all sectors of human life, especially the economic sector. The company organization as the main support for the economic sector must quickly respond to this condition. The Human Resources Department (HRD) as the division that manages human resources (HR) in corporate organizations has a very strategic role in efforts to maintain and improve employee competence so that the company can survive. Therefore, this article aims to obtain the necessary knowledge comprehensively related to the role and strategy of the Department of Human Resource Development (HRD) in an effort to increase employee competence during the COVID-19 pandemic and the new normal era in corporate organizations. This research method uses descriptive qualitative method with the type of library research (library research)